Geographical Information System (GIS) and Remote Sensing (RS) Applications in Disaster Risk Reduction (DRR) in Malaysia - Mohamad Abdullah, Nazirah; Sulaiman, Noralfishah; Nazir, Umber; Ismail, Maziah; Abdul Latib, Siti Kursiah Kamalia; Mahmud, Nur Putri Najwa (International Journal of Integrated Engineering, 2022)
In a world today that is highly dependent on information technologies, Geographical Information System (GIS) and Remote Sensing (RS) has become one of advancement in spatial technologies that had been used to tackle the issue of an uncertain world. Primarily functioned with specialized capabilities in manipulating, analyzing, and visualizing the massive data from multiagencies, has opened new avenues for these technologies to be adopted in disaster management. Taking this into consideration, it leads to achieving disaster management objectives in Disaster Risk Reduction (DRR) which to reduce or minimize the exposure to hazards, lessened vulnerability of people and property, wise emergency preparation, and enhanced preparedness for an unfavourable situation. This paper aims to make a systematic review of literature in highlighting the significant potential of the GIS and remote sensing, integrating the aspect relevant to disasters socially and physically that helps in forming a comprehensive disaster management operations to reduce the vulnerability and strengthen the resilience to disaster. Accordingly, the paper has presented the outcomes and review of several researchers concerning the implementation of GIS and remote sensing in disaster management, specifically on disaster risk reduction.